How enterprise risk management mediates the relationship between board size and corporate social responsibility: Evidence from GCC Islamic banks - Awatif Hodaed Alsheikh; Warda Hodaed Alsheikh; Tamader Alsalami (Banks and Bank Systems)
Corporate Social Responsibility is a crucial aspect of a company’s strategic plans. Stakeholders prioritize the social and environmental impacts of a company’s operations in their decision-making process regarding its performance. This has encouraged companies to begin voluntarily reporting annually on the social and environmental impacts of their businesses, which has become widely known as Corporate Social Responsibility Disclosure. The purpose of this study is to investigate the relationships between board size, enterprise risk management, and corporate social responsibility disclosure in Islamic banks listed on GCC stock markets. It also explores the role of enterprise risk management as a mediating variable in the relationship between board size and corporate social responsibility disclosure. The results show that larger board sizes are positively significant to increased corporate social responsibility disclosure and enterprise risk management using the fixed-effect regression analysis. Specifically, enterprise risk management completely mediates the linkage between board size and corporate social responsibility disclosure. Indeed, this positive relationship between the size of a board and enterprise risk management reinforces the argument from practice that larger boards provide better oversight of the management of risks. The robust enterprise risk management framework equips banks in a better position to identify social and environmental risks to the business and, consequently, contribute to more transparent corporate social responsibility disclosures. Thus, the larger boards are important for effective risk management and more transparency on issues of corporate social responsibility, which can improve the organization’s reputation and strengthen stakeholder confidence.